Experimental and simulation study of thermal accumulation in an enclosed vehicle - David Chua, S.N.; Chan, B.K.; Lim, S.F. (SAGE Publications Ltd, 2019)
Thermal accumulation in a car cabin under direct exposure to sunlight can be extremely critical due to the risk of heatstroke especially to children who are left unattended in the car. There are very limited studies in the literature to understand the thermal behaviour of a car that is parked in an open car park space and the findings are mostly inconsistent among researchers. In this paper, the studies of thermal accumulation in an enclosed vehicle by experimental and computational fluid dynamics simulation approaches were carried out. An effective and economical method to reduce the heat accumulation was proposed. Different test conditions such as fully enclosed, fully enclosed with sunshade on front windshield and different combinations of window gap sizes were experimented and presented. Eight points of measurement were recorded at different locations in the car cabin and the results were used as the boundary conditions for the three-dimensional computational fluid dynamics simulation. The computational fluid dynamics software used was ANSYS FLUENT 16.0. The results showed that the application of sunshade helped to reduce thermal accumulation at car cabin by 11.5%. The optimum combination of windows gap size was found to be with 4-cm gap on all four windows which contributed to a 21.1% reduction in car cabin temperature. The results obtained from the simulations were comparable and in agreement with the experimental tests.